ANALISIS PENGUNGKAPAN DAN DAMPAK PENERAPAN CORPORATE SOCIAL RESPONSIBILITY DI HOTEL THE WESTIN RESORT NUSA DUA - Permana Umawan, Anak Agung Ngurah Krisna; Dwija Putri, I G A M Asri (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
The Companies moved abaout tourism industry or hospitality sector today is equally to implement CSR activities. The development of CSR in the tourism sector, especially the hotel does not run as fast as the other business sectors. CSR is a form of corporate responsibility in correcting social inequality and environmental damage that occurs as a result of operational activities of the company. The method used is descriptive qualitative. The data used are annual reports obtained directly and through direct interviews with human resources staff Hotel. Discussion of the results showed that the application of CSR disclosure Hotel The Westin Resort Nusa Dua Bali in 2014 for all sectors other than energy have CSRDI value> 50%. Strong Basic Hotel The Westin Resort Nusa Dua Bali. Through social activities of the company, will make the company's name could be great in the eyes of the public at large.
Keywords: Basic, Impact, CSR Disclosure